Gastrointestinal perforations induced by long-term non-steroidal anti-inflammatory drugs use: a case series analysis and discussion - Pooja, Mydukuru; Kesavulu, Chennasamudram C.; Kumar, Jutla V.; Nikhat P., Yashmeen (International Journal Of Community Medicine And Public Health, 2024)
Non-steroidal anti-inflammatory drugs (NSAIDS) are used in a wide range but may cause harm to the gastrointestinal mucosa, which leads to various complications. This study shows the impact of long term NSAID use on small and large intestine and presents 2 cases of patients with NSAID induced perforations. The first case involves a 62-year-old male patient with RA on long term Ibuprofen use, presented with abdominal pain, vomiting, and lower limbs pain. Laparotomy revealed a 5 mm perforation in the proximal jejunum. The second case, a male patient of 65 years of age using diclofenac without a prescription, which lead to a 4×4 cm sigmoid colon perforation. The comparison of both the cases presents a difference in examination and laboratory findings. Long-term NSAID use has been associated with various GI complications, including perforations. The case presents the importance of considering NSAID related complications, mainly in older patients and the persons with ulcers. Combining NSAIDS with other drugs, like misoprostol may minimize the risk of the GI complications. NSAIDs are also linked with cardiovascular events, and heart related issues. This study shows the need of careful NSAID prescription, with their association with preventable adverse effects. 30% of hospitalizations for adverse drug reactions are only by the NSAIDs. PPIs and H2 receptor antagonist are commonly used to protect the gastrointestinal mucosa which minimizes the occurrence of ulcers. Healthcare professionals should be careful particularly in case of high risk patients to minimize the NSAID related complications.